2009
DOI: 10.1002/bmb.20299
|View full text |Cite
|
Sign up to set email alerts
|

Making ordered DNA and protein structures from computer‐printed transparency film cut‐outs

Abstract: Instructions are given for building physical scale models of ordered structures of B-form DNA, protein ahelix, and parallel and antiparallel protein b-pleated sheets made from colored computer printouts designed for transparency film sheets. Cut-outs from these sheets are easily assembled. Conventional color coding for atoms are used for both types of biopolymers. Arrows facilitate following chain direction for the polypeptides. For DNA, the 5 0 to 3 0 direction is guided by a 5 0 phosphate group and a free hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The high complexity of molecular structure in biological macromolecules exacerbates the difficulties students face using two‐dimensional (2D) molecular representations . These molecular structures and their properties, including solubility and biological function, are governed by noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high complexity of molecular structure in biological macromolecules exacerbates the difficulties students face using two‐dimensional (2D) molecular representations . These molecular structures and their properties, including solubility and biological function, are governed by noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…By using three‐dimensional representations, barriers to problems arising from translating between 2D and 3D can be removed . For example, studies that have developed physical models of biological macromolecules have used materials such as pipe cleaners to mimic chromosomes, clothespins to represent RNA, binder clips to represent amino acids or transparency cutouts for proteins and DNA . However, while the simplified structures in these physical models are easy to generate, they contain limited structural information .…”
Section: Introductionmentioning
confidence: 99%
“…This result is in accordance with the finding of Herman et al [17] that the physical models are very useful in introducing the basic concepts of protein structure to students. In addition, Jittivadhana et al [41] observed that the use of physical models was better to understand 3D features of proteins than the textbooks illustrations or computer graphic representations.…”
Section: Insulin As a Model To Teach Three-dimensional Structure Of Pmentioning
confidence: 99%
“…Students often appreciate hands-on activities, especially those that model three-dimensional processes or structures. Protein-folding models can be extremely simple and inexpensive, such as paper or overhead transparency plastic ( 4 , 7 ), or slightly more complicated, such as those made out of wire ( 13 ) or pipe cleaners, with pony beads or other small items to symbolize amino acids ( Fig. 1 ) ( 1 , 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%